Financial education for youth: A randomized evaluation in Uruguay - Fernando Borraz; Ana Caro; Maira Ca\~no-Guiral; María José Roa (Global Labor Organization (GLO), 2021)
Using data from a randomized control trial in Uruguay, we evaluate the impact of an economic and financial education program targeted to senior high-school students. The program is based on an innovative playful approach workshop about monetary policy and financial supervision. We find that the workshop has a positive and significant impact on student knowledge. Our results shed light on the importance of economic and financial education for the youth in developing countries.
Keywords: A21; D12; I22; J24; 330; BCUEduca; economic education; youth; treatment effects